1998
DOI: 10.1046/j.1365-2842.1998.00230.x
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the diagnostic value and estimation of the chaos phenomenon in masticatory movement using fractal dimension in patients with temporomandibular dysfunction syndrome

Abstract: The aim of this study was to estimate the chaos phenomenon (chaos) in masticatory movements using the fractal dimension (FD), and to examine the diagnostic value of the fractal dimension in comparing stomatognathic functional disturbances with normal stomatognathic function. The subjects were all high school students and included nine subjects presenting with acceptable normal occlusion, 18 subjects with TMJ dysfunction syndrome and seven subjects with tooth crowding. Masticatory movements were obtained during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…Morinushi et al [143] reported preliminary evidence of the potential use of fractal analysis to diagnose temporomandibular dysfunction syndrome. They followed the mandible motion during chewing and characterized motion complexity through a FD.…”
Section: Variousmentioning
confidence: 99%